The Discovery of Insulin-Regulated Aminopeptidase (IRAP) Inhibitors: A Literature Review - Dimitris Georgiadis; Angeliki Ziotopoulou; Eleni Kaloumenou; Angelos Lelis; Antonia Papasava (Frontiers Media S.A., 2020)
Insulin-Regulated Aminopeptidase (IRAP, EC 3.4.11.3) is a multi-tasking member of the M1 family of zinc aminopeptidases. Among its diverse biological functions, IRAP is a regulator of oxytocin levels during late stages of pregnancy, it affects cellular glucose uptake by trafficking of the glucose transporter type 4 and it mediates antigen cross-presentation by dendritic cells. Accumulating evidence show that pharmacological inhibition of IRAP may hold promise as a valid approach for the treatment of several pathological states such as memory disorders, neurodegenerative diseases, etc. Aiming to the investigation of physiological roles of IRAP and therapeutic potential of its regulation, intense research efforts have been dedicated to the discovery of small-molecule inhibitors. Moreover, reliable structure-activity relationships have been largely facilitated by recent crystal structures of IRAP and detailed computational studies. This review aims to summarize efforts of medicinal chemists toward the design and development of IRAP inhibitors, with special emphasis to factors affecting inhibitor selectivity.